Türk Dünyası Geleneklerinde Geçiş Dönemlerin (Doğum, Evlenme, Ölüm) Önemi - Kayhan, Shurubu (My University, 2018)
Even if society has inherent in any society habits, continues centuries-old traditions and customs of the unconscious life. Traditions are unique sources that show the inner world and worldview of one nation. They are an essential tool in the folk history learning, development stages and forming opinions of humankind since ancient times. Birth, marriage and death, as one of the most important and fundamental practices (events) in a person's life have particular importance. Talking about Turkish folks, about their identity, we have to mention importance of traditions and customs. For this reason, in our research we have studied Turkish folks’ customs that associated with childbirth, marriage and death. Traditions are the values that bind the past, present and future. These values do not appear spontaneously and a society, in which these values not protected, will not become a nation (folk). Features that distinguish one nation from others, and that formed over a long period required to transmit these traditions from generation to generation, so that the society continued its existence. When assessing the cultural continuity, we see that the Turkish people largely managed to preserve many traditions and way of life until nowadays. No matter who you are and what social status you have, respect for customs and traditions among the Turkish people is the most important duty. Therefore, the Turkish folks’ traditions, being originally a public rule, have great authority and preserved. However, some of them belonging to certain religious beliefs over time have changed either disappeared altogether.
Keywords: Türk Dünyası; Türk Kültürü; Gelenek ve Görenekler; Doğum; Evlilik; Evlilik; Turkish World; Turkish Culture; Traditions and Customs; Birth; Merriage; Death